Crossing Borders, Claiming a Nation : A History of Argentine Jewish Women, 1880-1955 - Deutsch, Sandra McGee, 1950- (Book collections on Project MUSE., 2010)
Historical analysis of Jewish women's role in Argentina from the late 19th through the first half of 20th century, arguing that they crossed racial, gender-based, and ideological boundaries as they helped shape the nation.